Situación y necesidades de la pequeña y mediana empresa (2005)
Today; it is considered very important the action of the small business in the Colombian economy. After the 90 s; it was recognized that many small business in Colombia were acting whithin an unknown and disperse way; without almost any protection or help; despite of the fact that they were contributing substantially to the national production. It is estimated that there are more that one million small business (Micro-Pymes) that contribute with more than fifty percent to the GNP and generate more that seventy percent of the national employment. There are great majority small businesses (Pymes) without any legal registration and only a small percent are registrated with a full compliance of the legal requirements. The School of Business and Entrepreneurial Sciences of the Universidad Sergio Arboleda; has decided to develop research about the reality of the Colombian Pymes (small business); in order to extend the knowledge and the potentiality of this companies. To get precise information about those companies it s a very difficult task because the great majority of the Pymes are not registered; and consequently there is not information or statistics about them. So the university should investigate the universe of the small business through surveys with a good methodology and analysis. The obtained results may suggest good recommendations for the issue of social an economic policies. The present essay formulates eleven punctual proposals that may lead to beneficial actions in favor of the Pymes.